Attenuated Oral Typhoid Vaccine Ty21a Elicits Lamina Propria and Intra-Epithelial Lymphocyte Tissue-Resident Effector Memory CD8 T Responses in the Human Terminal Ileum - Booth, Jayaum S.; Patil, Seema A.; Goldberg, Eric; Barnes, Robin S.; Greenwald, Bruce D.; Sztein, Marcelo B. (Frontiers in Immunology, 2019)
Tissue-resident memory T cells (TRM) are newly defined memory T cells (TM) distinct from circulating TM subsets which have the potential to mount rapid protective immune responses at the site of infection. However, very limited information is available regarding the role and contribution of TRM in vaccine-mediated immune responses in humans at the site of infection. Here, we studied the role and contribution of tissue resident memory T cells (TRM) located in the terminal ileum (TI) (favored site of infection for S. Typhi) following oral Ty21a immunization in humans. We examined TI-lamina propria mononuclear cells (LPMC) and intra-epithelial lymphocytes (IEL) CD8+ TRM subsets obtained from healthy volunteers undergoing medically-indicated colonoscopies that were either immunized with Ty21a or unvaccinated. No significant differences in the frequencies of LPMC CD8+ TRM and CD8+CD69+CD103- T cells subsets were observed following Ty21a-immunization. However, LPMC CD8+ TRM exhibited significantly higher levels of cytokines (IFN, IL-17A, and TNF) ex-vivo in Ty21a-vaccinated than in unvaccinated volunteers. LPMC CD8+ TRM S. Typhi-specific responses were evaluated using S. Typhi-infected targets and found to produce significantly higher levels of S. Typhi-specific IL-17A. In contrast, LPMC CD8+CD69+CD103- T cells produced significantly increased S. Typhi-specific levels of IFN, IL-2 and IL-17A. Finally, we assessed CD8+ TRM in IEL and observed that the frequency of IEL- CD8+ TRM is significantly lower following Ty21a immunization. However, ex-vivo IEL- CD8+ TRM elicited by Ty21a immunization spontaneously produced significantly higher levels of cytokines (IFN, IL-17A, IL-2 and TNF). This study provides the first demonstration of the effect of oral Ty21a vaccination on CD8+ TRM subsets (non-specific and S. Typhi-specific) responses in the LPMC and IEL compartment of the human terminal ileum mucosa, contributing novel information to our understanding of the generation of mucosal immune responses following oral Ty21a-immunization.